Diseño y análisis de costos de un sistema de gestión ambiental, seguridad y salud en el trabajo para el proyecto de limpieza de canales y quebradas en la ciudad de Bogotá D.C. (2016)
The present work is based on the analysis of environmental management systems and health and safety at work that are being designed and implemented in the cleaning project of canals and streams of the city of Bogotá under the interadministrative agreement 430 of 2014, using as a basis the ISO 14001: 2015, OHSAS 18001: 2007 and Decree 1072 of 2015, in order to find the flaws that have not allowed the full implementation of the systems to generate actions that allow compliance with the requirements of the same and associated costs, so that the process can be planned and resources managed to minimize risks, contribute to employee welfare, increase the company's productivity, without generating negative impacts on the environment in the path of mitigation and adaptation to climate change. The first thing that was developed was the identification of the requirements of the standards, ISO 14001: 2015, OHSAS 18001: 2007 and Decree 1072 of 2015, for the construction of a checklist for each of the standards. Afterwards, a diagnosis of the situation of the project against the norms was made, with the realization of field visits and the application of the previously constructed tool. From the application of the checklists, the shortcomings were identified against the norms, generating activities that would lead to compliance with the associated requirements. The proposed activities were planned and quantified in a cost schedule, which was entered into the budget to result in the total investment required by the organization to comply with the rules in the channel and stream cleaning project, so that they can initiate steps that lead to the completion of the process in a planned manner.